2023
DOI: 10.3390/nu15092155
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Weight Management to Prevent the Developmental Programming of MAFLD in Offspring of Obese Mothers

Abstract: The global surge of obesity amongst women of reproductive age has raised concerns surrounding the health consequences for their offspring as there is a formidable link between an obesogenic maternal environment and the developmental programming of metabolic dysfunction in the offspring. Specifically, the offspring of mothers with obesity have a three-fold higher risk of developing metabolic-associated fatty liver disease (MAFLD) compared to the offspring of healthy-weight mothers. Given the burgeoning burden o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
0
0
Order By: Relevance
“…Evidence from epidemiological, clinical, and animal studies have demonstrated that obesity affects not only maternal health, but also the long-term outcomes of offspring, with increased risk of obesity and cardiovascular disease (CVD) later in life [2][3][4]. Although the exact mechanisms of the transgenerational effect of maternal obesity remains unclear, fetal programming has been suggested to play a pivotal role in this process [5][6][7]. Human studies have provided evidence for the mechanisms underlying the link between maternal obesity and offspring cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from epidemiological, clinical, and animal studies have demonstrated that obesity affects not only maternal health, but also the long-term outcomes of offspring, with increased risk of obesity and cardiovascular disease (CVD) later in life [2][3][4]. Although the exact mechanisms of the transgenerational effect of maternal obesity remains unclear, fetal programming has been suggested to play a pivotal role in this process [5][6][7]. Human studies have provided evidence for the mechanisms underlying the link between maternal obesity and offspring cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%